Citizen Curators: Cultural Democracy in Action?. Issue 1 (1st July 2022) - Goskar, Tehmina
Abstract: This article presents findings and reflections of the Citizen Curators program, designed and led by the author on behalf of Cornwall Museums Partnership and seven participating museums. Dubbed an experiment in cultural democracy, as well as providing a novel alternative pathway into museum work, Citizen Curators took place between 2017 and 2021 with four cohorts resulting in more than 80 successful completers, one-fifth of whom went on to jobs in the sector. The program was designed as an action research project in curatorial education in an era of equity, socially engaged practice, and ethical awareness. The article presents qualitative and quantitative findings on the program's design, impact, and what was learned about the realities of cocuration, diversity, and inclusion over the four-year program.